Medication adherence among allogeneic haematopoietic stem cell transplant recipients: a systematic review protocol - Alvisa Palese; Irene Mansutti; Chiara Visintini (BMJ Open, 2022)
Introduction Patients receiving a haematopoietic stem cell transplant (HSCT) are subjected to complex oral medications based on prophylactic and immunosuppressive treatments. Adherence to medication plays a role in survival, and medication non-adherence (MNA) is closely associated with graft-versus-host disease and other complications. The aim of this systematic review is to summarise the available evidence regarding prevalence rates of medication adherence, the risk factors of MNA, the effectiveness of interventions to increase medication adherence and the outcomes associated with MNA.Methods and analysis We designed a systematic review according to the Joanna Briggs Institute methodology. We will search the Cochrane Library and the CINAHL, EMBASE, MEDLINE via PubMed, PsycINFO and Scopus databases. We will include published and unpublished primary studies: (a) on humans, from inception until 10 May 2022; (b) written in any language; (c) experimental (randomised and non-randomised), observational (prospective, retrospective cohort and case–control), correlational, cross-sectional and longitudinal; and (d) with a low risk of bias, according to the quality assessment we perform. We will exclude secondary and qualitative studies, protocols, publications without original data, including paediatrics or related to autologous HSCT. The primary outcome will be the prevalence of oral medication adherence; the secondary outcomes will be the risk factors of MNA, the interventions aimed at increasing medication adherence and the outcomes of MNA. Two researchers will independently screen the eligible studies, then extract and describe the data. Disagreements will be resolved by a third researcher. We will provide a qualitative narrative synthesis of the findings.Ethics and dissemination Ethical approval is not required given that previously published studies will be used. We will disseminate the findings through conference presentations and publications in international peer-reviewed scientific journals.PROSPERO registration number CRD42022315298.